Peningkatan Asupan Energi dan Lemak saat Akhir Pekan pada Remaja - Humaira, Arisya; Adi, Annis Catur (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Overweight is defined as an excessive or abnormal accumulation of body fat that impacts health risks. Data of riskesdas indicated that prevalence of adolescent with overweight in Surabaya was higher than National prevalence is 14,46% in 2018. Epidemiological studies indicated an increase in energy and fat intake in adolescents on weekend which leads to the risk of overweight. The purpose of this study was to analyze the difference in energy and fat intake between adolescent with overweight and normal weight and its correlation with adolescent nutritional status at SMAN 5 Surabaya. This quantitative study used observational method with case control design. The sample size was 48 students consisting of 24 student in each case and control group. The data were analyzed using T test and schi square with significance level Î±<0,05. The result of statistical test indicated a difference in fat intake on weekend (p=0,008), correlations between increased energy intake (p=0,000) and fat intake (p=0,000) on weekend with the nutritional status of adolescents. Adolescent are advised to pay more attention to the quality intake on the weekend by taking low energy food or reducing the amount of high energy and fat food consumption.